The enthalpy of mixing of the laurylmethacrylate with some organic solvents - Serheyev, Valentyn (Publishing House of Lviv Polytechnic National University, 2015)
The enthalpy of mixing for the binary systems of the laurylmethacrylate with hexane, benzene, 1,2- diclorethane and acetic acid have been measured as a function of their concentration, the temperature of 293K and at the atmospheric pressure, by the calorimetric methods. The concentration dependences of the enthalpies of mixing were correlated by polynomials. For the system acetic acid–laurylmethacrylate the enthalpies of mixing were positive for all concentrations, while for other systems the enthalpies of mixing takes were positive only when the solvent concentration was greater than 25 mol%. Калориметричним методом визначені ентальпії змішування бінарних систем лаурилметакрилату з гексаном, бензеном, 1,2-дихлоретаном та оцтовою кислотою за температури 293 К та атмосферного тиску. Концентраційні залежності ентальпії змішування апроксимовані степеневими поліномами. Для системи оцтова кислота - лаурилметакрилат ентальпія змішування набуває додатних значень у всьому дослідженому діапазоні концентрацій, а для решти досліджених систем ентальпія додатна для концентрацій розчинника вищих за 25% мол.
Ентальпії змішування лаурилметакрилату з деякими органічними розчинниками
Keywords: solution; calorimetric method; enthalpy of mixing; laurylmethacrylate; hexane; benzene; 1,2-diclorethane; acetic acid; розчин; калориметрія; ентальпія змішування; лаурилметакрилат; гексан; бензен; 1,2-дихлоретан; оцтова кислота